The application of organoids in colorectal diseases - Liu, Yanxin; Wang, Dongxu; Luan, Yanhong; Tao, Boqiang; Li, Qirong; Feng, Qiang; Zhou, Hengzong; Mu, Jianfeng; Yu, Jinhai (Frontiers in Pharmacology, 2024)
Intestinal organoids are a three-dimensional cell culture model derived from colon or pluripotent stem cells. Intestinal organoids constructed in vitro strongly mimic the colon epithelium in cell composition, tissue architecture, and specific functions, replicating the colon epithelium in an in vitro culture environment. As an emerging biomedical technology, organoid technology has unique advantages over traditional two-dimensional culture in preserving parental gene expression and mutation, cell function, and biological characteristics. It has shown great potential in the research and treatment of colorectal diseases. Organoid technology has been widely applied in research on colorectal topics, including intestinal tumors, inflammatory bowel disease, infectious diarrhea, and intestinal injury regeneration.This review focuses on the application of organoid technology in colorectal diseases, including the basic principles and preparation methods of organoids, and explores the pathogenesis of and personalized treatment plans for various colorectal diseases to provide a valuable reference for organoid technology development and application.